SOCIAL ISSUES IN JACQUES LOB’S “SNOWPIERCER” - Monica Alivia Hani Pratiwi (Anaphora : Journal of Language, Literary, and Cultural Studies, 2021)
This study entitled “Power Relation In Jacques Lob’s Snowpiercer” is about social issues between passengers in front sections to tail sections, depicted through the story and characters in this novel. In this study, there are two questions to be answered: The forms of power relationships shown in Jacques Lob's novel Snowpiercer and the individuals involved. The purpose of this study is to look at the many forms of power relationships and the persons that are involved in them using numerous characters from the novel. The author applies Michel Foucault's (1977) theory to illustrate how passengers in front and back sections interact in terms of power. The descriptive technique is used in this study, and extrinsic approaches are used. The findings reveal that there are two distinct forms of power relationships. To begin with, sovereign power is a sort of authority that has total control over all persons in a community. Second, disciplinary authority seeks to establish discipline bodies. The outcome also exposes that certain characters have manipulated information and truth via the use of power relationships.